2016
DOI: 10.1016/j.matdes.2016.09.079
|View full text |Cite
|
Sign up to set email alerts
|

Grain orientation statistics of grain-clusters and the propensity of multiple-twinning during grain boundary engineering

Abstract: Large grain-cluster or so-called twin-related domain is a typical characteristic of the grain boundary (GB) engineered microstructure. Grain-cluster is formed via numerous twinning operations starting from single nucleus, and the process is referred to as multiple-twinning. This work investigated the orientation diversity within grain-clusters and the twinning ordering of multiple-twinning based on the statistics of grain-orientations in 30 large-sized grain-clusters from GB-engineered Ni-based alloy 690. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The sizes range from 37 to 44 μm, and the average grain size for the 14 maps is 41 μm. If the twin-related ( 3 n -type) boundaries were excluded from the size calculation, the sizes of TRDs (TRDs) were obtained [28,[32][33][34][35][36][37]. The result is showed in Figure 4(b).…”
Section: Microstructures On Serial Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sizes range from 37 to 44 μm, and the average grain size for the 14 maps is 41 μm. If the twin-related ( 3 n -type) boundaries were excluded from the size calculation, the sizes of TRDs (TRDs) were obtained [28,[32][33][34][35][36][37]. The result is showed in Figure 4(b).…”
Section: Microstructures On Serial Sectionsmentioning
confidence: 99%
“…For example, Lind et al [27] explored the TRDs in conventionally processed and GB-engineered copper, obtaining that the numbers of grains of the largest TRDs in GBE samples are nearly 10 times more than that of conventional samples. TRD can be topologically represented by a tree-shape twin-chain [27,28,32,34,35], which is closely correlated with multiple-twinning [14,27,32,34] that is the process to form the TRD. However, overall these studies were based on two-dimensional (2D) characterisation on cross-sections except a recent study performed by Lind et al [27] who compared the three-dimensional (3D) TRDs of GBE and conventional copper.…”
Section: Introductionmentioning
confidence: 99%
“…In order to analyze the mutual misorientations between any two grains inside of the cluster, eight grains were randomly selected, and the results are listed in Table II and Table III. The detailed analyzing of all the mutual misorientations between any two grains in the grain-cluster was reported elsewhere [23,33] . It can be demonstrated that all grains in cluster have ∑3 n misorientations regardless of whether they are adjacent.…”
Section: Grain Boundary Network Evolution During Recrystallization Anmentioning
confidence: 99%
“…This has a positive and important guiding significance for the preparation of nanocrystalline alloys with excellent comprehensive properties of high strength and high plasticity. [3] In addition, the short-range ordered structure of multielement alloys, such as medium-entropy alloys and high-entropy alloys, makes them have good properties and plays an increasingly important role in various industrial products and applications. [4] Adding light-alloy Al into the superalloy Ni-Co alloy can design and prepare NiCoAl medium-entropy alloy with good hightemperature resistance, wear resistance, oxidation resistance, low density, lightweight, high magnetism, and good wave absorption performance.…”
Section: Introductionmentioning
confidence: 99%
“…This has a positive and important guiding significance for the preparation of nanocrystalline alloys with excellent comprehensive properties of high strength and high plasticity. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%